Analisa Erosi Embung Putukrejo Menggunakan Metode Usle - Hanggara, Ikrar; Irvani, Harvi (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
Small DAM is an effort to conserve water. One of the problems that arise in Small DAM is sedimentation due to land erosion which results in reduced reservoir and age to use the reservoir. Putukrejo reservoir is an effort to overcome the drought that occurred in Putukrejo Village. In this study the researcher intends to study the erosion of land that has the potential to occur in the reservoir and find out the erosion categories that occur. The method used to carry out pond erosion rate analysis using the USLE method (Universal Soil Lost Equation). With this method, the average erosion rate for embung watershed is 25.4 tons / ha / year and the figure is categorized as light erosion.